1999
DOI: 10.1007/s004670050599
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E ε 4 allele and nephrotic glomerular diseases in children

Abstract: Hyperlipidemia is a well-recognized complication of the nephrotic syndrome and is a factor contributing to the progression of the initial glomerular injury and the development of glomerulosclerosis. Apolipoprotein E (apoE) is a plasma protein and apoE epsilon 4 allele is associated with higher plasma cholesterol levels. With this in mind, we studied apoE phenotypes and alleles in children with nephrotic glomerular diseases (NGD, n=29), including idiopathic nephrotic syndrome (n=16), membranoproliferative glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…48 Therefore several studies investigated an association between the apo E polymorphism and NS in humans, and had contrasting findings. Smaller studies found an increase in the ⑀4 allele in childhood NS, 49 which was not confirmed by 2 larger studies. 50,51 A recent study found a tendency toward a higher frequency of ⑀4 allele in 190 nephrotic children, which became significant in those who had frequent disease relapses.…”
Section: Apo E Polymorphismmentioning
confidence: 88%
“…48 Therefore several studies investigated an association between the apo E polymorphism and NS in humans, and had contrasting findings. Smaller studies found an increase in the ⑀4 allele in childhood NS, 49 which was not confirmed by 2 larger studies. 50,51 A recent study found a tendency toward a higher frequency of ⑀4 allele in 190 nephrotic children, which became significant in those who had frequent disease relapses.…”
Section: Apo E Polymorphismmentioning
confidence: 88%
“…Serum levels of apo E were increased in nephrotic patients compared with normal controls, whereas apo E levels very low in urine. The genotype of apo E was in all cases E3/E3 encoding apo E 3 , the most frequent genotype (13).…”
Section: P Alb Inhibitorsmentioning
confidence: 92%
“…It has been demonstrated that components of HDL inhibit glomerular albumin permeability induced by serum from patients with FSGS (25). Genetic variants of HDL components have been associated to idiopathic FSGS, such as ApoE (26) or paraoxonase (27), and specially the apolipoprotein L1 (28). This would result in altered HDL particles, which have been implicated in the pathogenesis of FSGS (29).…”
Section: Discussionmentioning
confidence: 99%